The Behaviour of the Military Battery Type BB248/U Used to Start the Engine of the A.P.C. - Brossard,Louis; Gallop,Lloyd (1979)
The performance of the lead-acid battery used to start the diesel engine in the Armoured Personnel Carrier (APC M113A1) was tested between -18 and -26 C. The lowest ambient temperature at which a start can be achieved without the assistance of slave batteries is close to -20 C provided the initial temperature of the vehicle batteries is about -15 C. The average cranking current under these conditions is approximately 450A and 13Ah are expended during a cranking period of close to 2 min. Engine starting is difficult or impossible if the terminal voltage (TV) is below 16V. The use of auxiliary batteries, connected in parallel, increases the value of the TV and the start is easier. It was demonstrated that the charge passed through batteries during a charge period of 30 to 45 min. with the alternator-regulator system varies between 6.5 and 9.5 Ah. This is markedly lower than the charge required to obtain a start. The viscosity of the lubricating oil also influences the ability to acheive an engine start at low temperatures and two synthetic Arctic Grade lubricating oils were evaluated. (Author) Abstract in French.